Starting soccer - EDOM, Helen, Osborne, Mike (London: Usborne, 2003)
his title has been revised to include Usborne's innovative Internet links. It gives step-by-step advice in a helpful and clear format, teaching all the basics, from tackling to dribbling - covering everything a beginner needs to know.